Perception of cancer patients in palliative care about quality of life - Silmara Meneguin; Ticiane Dionísio de Sousa Matos; Maria de Lourdes da Silva Marques Ferreira
ABSTRACT Objective: To understand the perception of cancer patients in palliative care about quality of life and identify propositions for its improvement. Method: This is a quantitative research carried out with 96 patients in palliative care, admitted in a public hospital from March 2015 to February 2015. The interviews were transcribed and analyzed by the methodology Discourse of the Collective Subject. Results: Quality of life was tied to meanings of health, well-being, happiness and spirituality; however, family and financial problems also had an impact on the perception of the construct. Interventions aimed at the relief of suffering, possibility of return to work and resolution of problems had suggestions for improvement. Conclusion: The results indicate that the concept of quality of life is subjective, tied to personal values and influenced by the repercussions of the health-disease process. In addition, they can guide actions based on interdisciplinary assistance aimed at the real needs of these patients.